Who Cares about Relative Deprivation? - Ravallion, Martin; Lokshin, Michael (World Bank, Washington, DC, 2012)
Theories of relative deprivation predict negative welfare effects when friends and neighbors become better-off. Other theories point to likely positive benefits. The authors encompass both views within a single model, which motivates their tests using a survey for Malawi that collected data on satisfaction with life, own economic welfare, and the perceived welfare of friends and neighbors. Their methods help address likely biases in past tests found in the literature. In marked contrast to research for industrial countries, the authors find that relative deprivation is generally not a concern for most of their sample, although it does appear to matter to the comparatively well off. Their results provide a welfarist explanation for the priority given to absolute poverty in poor countries. The pattern of externalities also suggests that there will be too much poverty and inequality in this economy, even judged solely from the point of view of aggregate efficiency.